Nonpremixed Counterflow Flames: Scaling Rules for Batch Simulations - Thomas Fiala; Thomas Sattelmayer (Journal of Combustion)
A method is presented to significantly improve the convergence behavior of batch nonpremixed counterflow flame simulations with finite-rate chemistry. The method is applicable to simulations with varying pressure or strain rate, as it is, for example, necessary for the creation of flamelet tables or the computation of the extinction point. The improvement is achieved by estimating the solution beforehand. The underlying scaling rules are derived from theory, literature, and empirical observations. The estimate is used as an initialization for the actual solver. This enhancement leads to a significantly improved robustness and acceleration of batch simulations. The extinction point can be simulated without cumbersome code extensions. The method is demonstrated on two test cases and the impact is discussed.